Oxidases as Oxygen Scavengers in Hypoxic Conditions: A Kinetic Model - Paolo Bazzoli; Stefania Iametti; Dimitrios Fessas; Francesco Bonomi; Alberto Schiraldi (Molecules, 2023)
A simple kinetic model allowed for the description of the observed decay of the oxygen content in hypoxic aqueous samples with and without headspace, in the presence of glucose oxidase (Glucox) or laccase and their substrates (glucose for Glucox and ABTS for Laccase). The experimental tests involved both the direct measurement of the oxygen content with a fluorescence-based probe and the indirect stopped-flow spectroscopic detection of colored compounds generated from suitable chromogenic reagents. The complete depletion of dissolved oxygen occurred in the no-headspace samples, whereas some residual oxygen remained in a steady state in the samples with headspace. Simple pseudo-first-order kinetics was adequate to describe the behavior of the system, as long as oxygen was the rate-limiting compound, i.e., in the presence of excess substrates. The values of the kinetic constants drawn from best-fit routines of the data from both experimental approaches were quite comparable. The oxygen residues in the samples with headspace seemed related to the low solubility of O2 in the aqueous phase, especially if compared with the large amount of oxygen in the headspace. The extent of such residue decreased by increasing the concentration of the enzyme. The kinetic model proposed in this paper can be of help in assembling suitable sensors to be used for food safety and quality control.